Implementasi Permenko Nomor 1 Tahun 2022 Dalam Menyalurkan KUR Tanpa Agunan Terhadap Nasabah Di Kota Bengkulu - Ganefi; Wafiya (UNIB Press, 2024)
In order to accelerate the National Economic Recovery (PEN), one of them is to assist indistributing credit to micro, small, and medium enterprises (MSMEs). Based on PERMENKO No. 1 of2022, the government issued a policy: distribution of People's Business Credit (KUR) loan assistanceto Micro, Small and Medium Enterprises (MSMEs) players, providing that the loan prerequisite iswithout collateral. However, in implementing this government policy in the field, it turns out thatcreditors/banks still require that People's Business Credit (KUR) loans made by MSMEs still useadditional collateral, including a 10 million loan and at least one motorbike BPKB. For IDR 50million, the collateral is BPKB car or land/house certificate. Only after the PERMENKO No.1 of 2023issuance did the Bank completely exempt KUR recipients from the additional collateral guaranteerequirements in Bengkulu City.